Artificial Intelligence sebagai Media Komunikasi Edukatif dalam Interaksi Pembelajaran Pendidikan Agama Islam di Madrasah Aliyah - Faiqotul Isma Dwi Utami (Institut Agama Islam Uluwiyah Mojokerto Indonesia, 2024)
This study aims to examine the role of Artificial Intelligence (AI) as an educational communication medium in the interaction of Islamic Religious Education (IRE) learning at MA Darul Ma’arif. The research employed a qualitative approach using a case study design. Data were collected through classroom observations, in-depth interviews with IRE teachers and students, and analysis of relevant instructional documents. The findings indicate that AI is utilized by students as a supportive communication medium to enhance their understanding of Islamic learning materials, particularly in clarifying religious concepts, expanding learning resources, and facilitating self-directed learning. The integration of AI contributes to more dialogical and reflective learning interactions, encouraging students to actively engage in meaning-making processes related to Islamic teachings. However, the study also reveals that the teacher’s role remains essential in maintaining the accuracy, contextualization, and normative values of Islamic knowledge to prevent misconceptions. From a theoretical perspective, this study extends the application of Computer-Mediated Communication (CMC) theory within the context of Islamic education by demonstrating that AI functions not merely as a learning technology, but as a communication medium that mediates interaction, interpretation, and religious meaning construction. The findings offer important implications for the development of adaptive, critical, and value-based digital learning models in Islamic Religious Education.